The critical intersection of environmental and social justice: a commentary - Leslie Solomonian; Erica Di Ruggiero (BMC, 2021)
Abstract The global crises of ecological degradation and social injustice are mutually reinforcing products of the same flawed systems. Dominant human culture is morally obliged to challenge and reconstruct these systems in order to mitigate future planetary harm. In this commentary, we argue that doing so requires a critical examination of the values and narratives which underlie systems of oppression and power. We argue for the moral necessity of a socially just approach to the ecological crisis.